The cranial morphology of the temnospondyl Australerpeton cosgriffi (Tetrapoda: Stereospondyli) from the Middle–Late Permian of Paraná Basin and the phylogenetic relationships of Rhinesuchidae. (15th October 2015) - Eltink, Estevan; Dias, Eliseu V.; Dias‐da‐Silva, Sérgio; Schultz, Cesar L.; Langer, Max C.
Abstract : Stereospondyls are a diverse and morphologically distinctive clade of basal tetrapods that rapidly reached a global distribution and high abundance during the Early Triassic. Yet, the first stereospondyls appeared in the Middle–Late Permian of Gondwana, mostly represented by Rhinesuchidae. A ustralerpeton cosgriffi is a long‐snouted representative of the group and one of the most complete temnospondyls known from the Permian of South America. The elements attributed to Au . cosgriffi were recovered from the Middle‐Late Permian deposits of the Rio do Rasto Formation (Paraná Basin), in the Serra do Cadeado area of Brazil. Here, we review the cranial anatomy of the species, providing a comparative redescription, new anatomical data and previously unrecognized characters. A ustralerpeton cosgriffi is nested within Rhinesuchidae based on the anatomy of the tympanic cavity, but its long‐snouted condition is unique amongst rhinesuchids. Based on the recovered information and new morphological data, the systematic position of Au . cosgriffi was assessed using a new matrix of 221 characters; of which 196 were selected from previous studies and the remaining are newly proposed. The results show Rhinesuchidae divided into Rhinesuchinae and Australerpetinae. A unique tympanic cavity formed by a well posteroventrally projected tabular horn, stapedial groove, well‐developed oblique crest on the pterygoid, and a dorsal pterygoid crest (new term) characterizes the ear region of Rhinesuchidae. A ustralerpeton cosgriffi is the only undisputed Rhinesuchidae record outside southern Africa and the first long‐snouted Stereospondyli, and thus is useful in helping to understand the diversification of the stereospondyls during the Middle/Late Permian of Gondwana.